DYNAMICS OF CD34/CD45 POSITIVE CELLS CONCENTRATION IN PERIPHERAL BLOOD OF PATIENTS AFTER ORTHOTOPIC LIVER TRANSPLANTATION AND PARTIAL LIVER RESECTION - O. P. Shevchenko; O. M. Tsirulnikova; R. M. Kurabekova; S. A. Lugovskaya; E. V. Naumova; N. Sh. Muratova; I. E. Tsirulnikova; S. V. Gautier (Вестник трансплантологии и искусственных органов, 2011)
Number of CD34/CD45+ cells were determined in blood of pediatric recipients and adult living-related liver do- nors. It has been investigated 15 pairs of recipients (aged from 4 to 60 months) and donors (29 ± 5 years). All the children had liver cirrhosis caused by congenital and inherited diseases of hepatobiliary system. Concentration of CD34/CD45+ cells in venous blood of recipients was higher than in donors. In recipients level of CD34/CD45+ cells did not correlate with sex, age, weight and height but did correlate with some biochemical parameters related to liver function. After liver transplantation number of CD34/CD45+ cells did not change in peripheral blood of recipients. In donors partial liver resection did not cause statistically significant changes in number or concentration of CD34/CD45+ cells in blood. Presented data suggests that neither liver transplantation nor liver resection has remarkable influence on number of CD34/CD45 + cells in peripheral blood.